Pengembangan Model Pembelajaran dengan Mengintegrasikan Strategi Pembelajaran dan Media Pembelajaran pada Pokok Bahasan Struktur Atom - Siti Nurlani Harahap (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. The aim of this research was to develop new learning models which integrating between learning strategies and learning medias to the atomic structure subject. The research was done in the first state secondary vocational school of Talawi. The research population consisted of four classes. All of the population were used as the research samples, so there were four experiment classes. They were first class of experiment was taught by using cooperative learning model was integrated with computer animation media; the second class of experiment was taught by using game learning model was integrated with computer animation media; the third class of experiment was taught by using game learning model was integrated with card media and the fourth class of experiment was taught by using game learning model was integrated with card media. The result of this research showed that learning strategies had influence to the student learning result significantly. The learning media had influence to the student learning result significantly. There were interaction between learning strategy with learning media. The most optimum of learning model to increase student learning result was game learning model was integrated with card media. Keywords: cooperative, game learning, animation media